Pembelajaran Matematika dengan ICT Sebagai Sarana Pengembangan Kecerdasan Emosional Siswa Menuju Pembangunan Karakter Bangsa - Ibrahim, Mr (Jurnal Fourier, 2012)
Nowadays ICT is rising rapidly, although in fact the effort of mathematics teaching quality is still concerning in cognitive aspect while forgetting non-cognitive aspect. The neglect of affective aspect as well emotional quotient in mathematics teaching contributes to social situation that hamper national character development. So, the development of ICT must be preferred as an alternative for mathematics teaching in order to extend emotional quotient towards national character development. It stands to reason that due to the development of ICT has another side that is likely to increase emotional skills in social life.